Analysis Of Knowledge, Perceptions And Practices On The Prevention Of Bullying By Teachers In Primary And Junior High School Education Units - Kusuma Dewi, Putu Dian Prima; Megaputri, Putu Sukma; Tangkas, Ni Made Karlina Sumiari (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Indonesia sendiri merupakan salah satu negara dengan angka kekerasan di lingkungan sekolah yang tinggi, khususnya berupa perundungan. Perundungan ini tidak bisa dianggap sepele karena tanpa disadari dapat menimbulkan trauma pada korban dan adiktif pada pelaku perundungan, muaranya tentu berdampak pada kesehatan mental generasi bangsa Indonesia. Penelitian ini bertujuan untuk menganalisis terkait pengetahuan, persepsi dan praktik pencegahan perundungan yang dilakukan oleh guru di satuan pendidikan sekolah dasar dan sekolah menengah pertama yag dilakukan pada 228 guru wali kelas dan BK di Kabupaten Buleleng. Penelitian menggunakan rancangan crossectional dengan instrument berupa kuisioer dan lembar obeservasi. Hasil penelitian menunjukkan bahwa lama bekerja lebih dari 5 tahun terbukti memiliki nilai OR 0.41 dengan nilai p value 0.01 dengan reference ada kategori baik dalam praktik pencegahan perundungan di satuan pendidikan. Makna secara statistic nilai OR 0,4 bahwa setiap peningkatan 1 - 5 tahun masa kerja guru dapat meningkatkan praktik baik terkait pencegahan perundungan hingga 60%.Hasil ini memberikan rekomendasi untuk penguatan program pencegahan perundungan di sekolah perlu dilakukan secara berkala dan terprogram dengan melibatkan semua guru. Pemberian informasi terkait regulasi dna program perundungan juga sebaiknya melibatkan juga para guru muda dengan masa kerja kurang dari 5 tahun. Kata Kunci : Perundungan, Buleleng, Guru, Sekolah ABSTRACT Indonesia itself is one of the countries with a high rate of violence in the school environment, especially in the form of bullying. This bullying cannot be considered trivial because without realizing it it can cause trauma to the victim and addiction to the perpetrator of the bullying, which of course has an impact on the mental health of the Indonesian generation. This research aims to analyze the knowledge, perceptions and practices of bullying prevention carried out by teachers in elementary school and junior high school education units which were carried out on 228 homeroom and guidance counselor teachers in Buleleng Regency. The research used a cross-sectional design with instruments in the form of questionnaires and observation sheets. The results of the study showed that working for more than 5 years was proven to have an OR value of 0.41 with a p value of 0.01 with a reference to being in a good category in the practice of preventing bullying in educational units. The statistical significance of the OR value of 0.4 is that for every 1 - 5 year increase in teacher service life, good practices related to bullying prevention can increase by up to 60%. These results provide recommendations for strengthening bullying prevention programs in schools that need to be carried out periodically and in a programmed manner involving all teachers. Providing information related to regulations and bullying programs should also involve young teachers with less than 5 years of work experience. Key words: Bullying, Buleleng District, Teacher, School